A novel device to improve robustness of end plate beam–column connections: Analytical model development. (March 2022) - Shaheen, Mohamed A.; Foster, Andrew S.J.; Cunningham, Lee S.
Abstract: A novel device to increase rotational capacity of steel end plate beam–column connections is proposed. By inserting a steel sleeve with a designated length, thickness and wall curvature between the end plate and the washer, the load path between the end plate and the bolts can be interrupted, promoting a more ductile response. For a specific sleeve material and dimensions, the capacity of sleeve is controlled by the amplitude value. The sleeve develops severe plastic deformations and is crushed between the end plate and the washer at the plastic amplitude. This study proposes an analytical solution to predict the plastic amplitude for the sleeve with a circular wave form. The sleeve is mathematically represented using shell of revolution theories under axisymmetric load. To simplify the analysis, the sleeve material is analysed using the two-moment limited interaction yield condition and follows an idealised rigid-perfectly plastic material response. The comparison between the proposed analytical solution with validated FE models show that the plastic amplitude is accurately captured. However, the predicted rotational capacity is very conservative. Highlights: The proposed device constitutes a steel sleeve that is inserted between the end plate and the washer. The device can increase the rotational capacity of the order of 3 times the standard connection. An analytical solution is introduced to predict the behaviour of the novel device.